A Green Route: From Carbon Dioxide to Silyl Substituted Carbonate Electrolytes for Lithium-Ion Batteries. Issue 7 (22nd April 2015) - Philipp, Manuela; Bernhard, Rebecca; Gasteiger, Hubert A.; Rieger, Bernhard
Abstract : The cyclic carbonates 4-(trimethylsilyl)-1, 3-dioxolan-2-one, 4-(triethylsilyl)-1, 3-dioxolan-2-one and 4-[2-(trimethylsilyl)ethyl]-1, 3-dioxolan-2-one were synthesized via an environmentally friendly synthetic route and applied as electrolytes in lithium-ion battery half-cells. The synthesis was carried out by the catalyzed conversion of CO2 with epoxides using the nontoxic catalysts FeCl2 and tetra-n-butylammonium bromide. Investigations of the LiTFSI solutions with regards to ionic conductivity, viscosity and solvent-salt interaction by NMR spectroscopy reveal a structure-property relationship. Linear sweep voltammetry measurements indicate no decomposition of the silyl carbonates within the electrochemical window of commonly used electrode materials for lithium-ion batteries. The suitability of the compounds as battery electrolytes is shown by half-cell measurements with lithium iron phosphate. The 4-(trimethylsilyl)-1, 3-dioxolan-2-one solution not only exhibits the highest conductivity but also a high capacity with superior stability over more than 50 cycles.